RANCANG BANGUN RECTANGULAR PATCH ANTENA MIKROSTRIP DENGAN METODE ARRAY 8 ELEMEN YANG BEKERJA PADA FREKUENSI 11 GHZ - Hilmiah Hidayana; Syah Alam; Indra Surjati (Jurnal Elektro, 2019)
In this research, the design and fabrication of microstrip antennas with circular polarization was is done to overcome the deviation of the antenna polarization angles, using microstrip line fed with a coaxial probe for Microwave Radio applications that work on the 11 GHz frequency band. To be able to produce circular or circular polarization on each patch of antenna arranged in an array, then it is done bit by bit (iteration) with the truncated corner technique on the edges and angles of the rectangular patch to produce an Axial Ratio of dec 3 deciBell.The type of substrate used in this study is FR4 with a relative dielectric constant value (Ɛr) = 4.58 and thickness (h) = 1.6 mm. By adjusting the cutting angle on the side of the patch, a circular polarization is generated with an Axial Ratio of a software simulation result of 1.065 dB and a bandwidth of 900 MHz at a frequency of 11 GHz. The final result of antenna fabrication tested at the Indonesian Institute of Sciences (LIPI) Electronics and Telecommunications laboratory in Bandung on May 29, 2019 consisted of a return loss value of -20,14 dB and VSWR 1.22 on the 11000 MHz frequency. The radiation pattern measurement results in a Half Power Beam Width value of 20 ° and an antenna gain of 7.02 dBi.